Environmental pollution in urban market: the case of Bodijamarket Ibadan, Nigeria (2013)
Ibadan is one of the largest cities in Nigeria, whose rapid growth is yet to be followed with adequate planning aimed at preventing environmental pollution. Consequently, the challenges of living in a constantly polluted environment, associated with stench and discomfort resulting from this inadequacy remains a constant experience in Bodija Market (a leading food stuff market in Ibadan). The recurrence of these challenges and the examination of the methods of waste disposal adopted by sellers in Bodija, form the focus of this paper using the Health Belief Model and Social Action Theory as bases for explanation. The study also revealed illiteracy, ignorance, negligence and laziness as major predisposing factors that aided sellers dumping of refuse in the environment. Personal hygiene and attempts to keep their immediate surrounding clean were reported as strategies adopted for prevention of environmental pollution which was observed to be inadequate. As a result, most sellers were willing to pay reasonable fee to prevent dirty environment in order to avoid dire consequences. The study recommends improved government effort, education, sanctions, sensitization and campaign against environment pollution to rescue the situation